2017
DOI: 10.3945/an.117.016261
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Factors Affecting Adult Neurogenesis and Cognitive Function

Abstract: Adult neurogenesis, a complex process by which stem cells in the hippocampal brain region differentiate and proliferate into new neurons and other resident brain cells, is known to be affected by many intrinsic and extrinsic factors, including diet. Neurogenesis plays a critical role in neural plasticity, brain homeostasis, and maintenance in the central nervous system and is a crucial factor in preserving the cognitive function and repair of damaged brain cells affected by aging and brain disorders. Intrinsic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
137
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(141 citation statements)
references
References 117 publications
(119 reference statements)
2
137
0
2
Order By: Relevance
“…Such focus could lead to discoveries that will improve health. The prospect of improved and continuous proliferation and generation of new neurons that improves the plasticity of adult mammalian brains could provide substantial therapeutic potential to treat neurodegenerative diseases and other disorders of the central nervous system (Poulouse, Miller, Scott, & Shukitt‐Hale, ).…”
Section: Resultsmentioning
confidence: 99%
“…Such focus could lead to discoveries that will improve health. The prospect of improved and continuous proliferation and generation of new neurons that improves the plasticity of adult mammalian brains could provide substantial therapeutic potential to treat neurodegenerative diseases and other disorders of the central nervous system (Poulouse, Miller, Scott, & Shukitt‐Hale, ).…”
Section: Resultsmentioning
confidence: 99%
“…Growing preclinical and clinical evidence has shown that diet and physical activity are key to maintaining brain health and cognitive function, especially during ageing . Nutritional factors in particular, may stimulate adult neurogenesis and help to protect cognitive function in the elderly, as well as those with brain disorders . However, the evidence for the link between cognition and diet/nutrition in BD is scarce, although findings from a recent 6‐week randomized trial did indicate that an adjunctive nutraceutical, creatine monohydrate, was associated with improved verbal fluency in depressed BD patients …”
Section: Emerging Correlates Of Cognitive Impairment In Bdmentioning
confidence: 99%
“…140 Nutritional factors in particular, may stimulate adult neurogenesis and help to protect cognitive function in the elderly, as well as those with brain disorders. 141 However, the evidence for the link between cognition and diet/nutrition in BD is scarce, although findings from a recent 6-week randomized trial did indicate that an adjunctive nutraceutical, creatine monohydrate, was associated with improved verbal fluency in depressed BD patients. 142 Finally, BD is associated with substantial rates of alcohol/substance misuse, which in turn may further worsen patients´ cognitive function, especially in the executive and verbal memory domains.…”
Section: Besides Sedentary Behaviour and Physical Inactivity Abnormalmentioning
confidence: 99%
“…Its antioxidant mechanisms explain its ability to improve memory in many of these studies, including via reduced oxidative damage through enhancing glutathione (GSH) and decreasing lipid peroxide levels in brain tissue (Perry & Howes, ; Sarker & Franks, ; Williams et al, ). Animal studies also show curcumin improves memory tasks and it can reverse stress‐induced reductions in neurogenesis, associated with brain‐derived neurotrophic factor (BDNF; Poulose, Miller, Scott, & Shukitt‐Hale, ). In the well‐established scopolamine model to assess memory retrieval in vivo , curcumin (50 or 100 mg·kg −1 orally for 10 days) restored the induced memory deficits in mice and prevented the scopolamine‐induced changes in Akt/glycogen synthase kinase‐3β, which is significant as the latter has been implicated in neurodegeneration and impaired cholinergic function (SoukhakLari, Moezi, Pirsalami, Ashjazadeh, & Moosavi, ).…”
Section: Phytochemicals As Nutraceuticalsmentioning
confidence: 99%
“…As the ageing process and neurodegenerative diseases have been characterised as pro-inflammatory states (Nelson & Tabet, 2015;Poulose et al, 2017), anti-inflammatory mechanisms of curcumin may also underpin its relevance to ameliorate cognitive decline (Table 1).…”
Section: Isoflavonesmentioning
confidence: 99%